Analisis Kelembagaan Pengelolaan Zakat Dan Fungsi Sosial Perbankan Syariah - Adiyes Putra; Nurnasrina Nurnasrina (JOURNAL OF SHARIA ECONOMICS, 2020)
Institutional zakat in Islamic banking has been regulated in Article 4 Paragraph 2 of Law No. 21 of 2008 concerning Islamic Banking. Where in that article Islamic banks are allowed to perform social functions in the form of collecting zakat, donations, alms, grants, or other social funds. The activities of Islamic banks conducting social activities become additional activities for Islamic banks. In contrast to the main function of Islamic banks as an intermediary function such as the collection and distribution of public funds that are required for Islamic banks to do so, while the social functions of Islamic banks only written in the Islamic banking Act can run, meaning that Islamic banks can choose between performing social functions or not doing it. The uncertainty of the Sharia Banking Law in regulating social functions makes Islamic banks not full of seriousness in carrying out these social functions. The lack of seriousness of this Islamic bank can be seen from the 14 Sharia Commercial Banks (BUS), only 10 BUSs that carry out social functions, and there are still 4 BUSs that have not yet performed social functions. The total funds that have been successfully collected and utilized by 10 BUS in the last 2 years are in 2017 Islamic banks collect zakat funds of Rp. 76.7 billion or 1.23% of the total funds raised by BAZNAS and LAZ (Rp. 6.22 trillion). In 2018 the collection of zakat funds through BUS experienced an increase of 16% from 2017 or collected Rp. 88.9 billion or 1.1% of the total zakat funds raised by BAZNAS and LAZ (Rp. 8.1 trillion). When compared to the amount of zakat fund raised by this BUS with the potential for national zakat totaling Rp. 217 Trillions, of course the achievement is not up to 1%, this means that the collection of zakat funds by the BUS is still far from expectations. Keywords: Zakat Institution, Social Function, Zakat, Islamic Bank